Analytic Hierarchy Process in Risk Assessment: A Bibliometric Perspective - Faradillah Febriyanti; Inggit Istani Putri; Muhammad Eko Wahyudi; Putri Nandira; Queen Firakirana Ramadhani; Via Zahwa Niagara; Lusiana Desy Ariswati; Muhammad Ramadhani Kesuma (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyses the development of research on the application of the Analytic Hierarchy Process (AHP) in risk assessment through a bibliometric approach. Data were collected from the Scopus database using relevant keyword combinations, yielding 1,685 articles. Analysis was conducted using VOSviewer to examine publication trends, author collaboration networks, and keyword co-occurrence patterns. The findings reveal that AHP in risk assessment has experienced significant growth and exhibits a high degree of international collaboration. The most frequently occurring keywords include "AHP," "risk assessment," and "fuzzy AHP," indicating a paradigm shift towards uncertainty-based and hybrid methodological approaches. This study maps the evolution of research themes and identifies future research directions, particularly concerning the integration of AHP with advanced analytical methods and sustainability issues. The bibliometric patterns identified here complement an expanding body of literature linking decision-science methods with financial management and organisational governance.